2013
DOI: 10.1002/jcp.24272
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and molecular characterization of the human Osteosarcoma 3AB‐OS cancer stem cell line: A possible model for studying osteosarcoma origin and stemness

Abstract: Finding new treatments targeting cancer stem cells (CSCs) within a tumor seems to be critical to halt cancer and improve patient survival. Osteosarcoma is an aggressive tumor affecting adolescents, for which there is no second-line chemotherapy. Uncovering new molecular mechanisms underlying the development of osteosarcoma and origin of CSCs is crucial to identify new possible therapeutic strategies. Here, we aimed to characterize genetically and molecularly the human osteosarcoma 3AB-OS CSC line, previously s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 54 publications
5
54
0
1
Order By: Relevance
“…Moreover, the presence of OS stem-like cells has been reported in patient tumors [62] as well as in established human OS cell lines [63]. We have previously shown [11,13,14] that 3AB-OS cells highly express a large panel of stemness-related genes/proteins and that efficiently transdifferentiate in vitro into cells of all the three primary germ layers [12], whereas when 3AB-OS cells were engrafted in nude mice, they potently induced malignant tumors, although preserving multilineage commitment [13]. Here, we show that, after in vitro 3AB-OS differentiation, in each derived cell lineage, p53-R248W/P72R was profoundly down-regulated and after p53-R248W/P72R-knockdown the expression of pluripotent markers (Oct3/4, Nanog, Sox2, nucleostemin and CD133) markedly lowered, suggesting that p53-R248W/P72R might be responsible for 3AB-OS cells pluripotency and self-renewal.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Moreover, the presence of OS stem-like cells has been reported in patient tumors [62] as well as in established human OS cell lines [63]. We have previously shown [11,13,14] that 3AB-OS cells highly express a large panel of stemness-related genes/proteins and that efficiently transdifferentiate in vitro into cells of all the three primary germ layers [12], whereas when 3AB-OS cells were engrafted in nude mice, they potently induced malignant tumors, although preserving multilineage commitment [13]. Here, we show that, after in vitro 3AB-OS differentiation, in each derived cell lineage, p53-R248W/P72R was profoundly down-regulated and after p53-R248W/P72R-knockdown the expression of pluripotent markers (Oct3/4, Nanog, Sox2, nucleostemin and CD133) markedly lowered, suggesting that p53-R248W/P72R might be responsible for 3AB-OS cells pluripotency and self-renewal.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, analyses of death receptors in OS samples and in OS cell lines-among which MG63 cells-demonstrated alterations only within the DR4 gene, suggesting that these genetic alterations may be implicated in OS formation [58]. We have previously shown that 3AB-OS cells highly express a great number of genes required for inhibiting apoptosis [11] and much lower levels of FAS and DR4 receptors than parental MG63 cells [14]. Here we show that in 3AB-OS cells p53-R248W/P72R-knockdown potently increases the expression of DR4 and DR5 receptors and sensitivity to TRAIL-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the basis of these characteristics, such as acquired resistance to cytotoxic chemotherapy agents for the overexpression of ATP-binding cassette multidrug efflux transporters 28,32,33 , or for the upregulation of the expression of detoxification enzymes such as ALDH 32 , for the expression of a particular surface marker, such as CD133, CD44, CD34, CD90, and others 30,34,35,41 , several different methods to isolate CSCs have been developed [42][43][44] . One of these techniques is the sphere formation assay, which is based on the capacity of CSCs to grow under non-adherent conditions.…”
Section: Discussionmentioning
confidence: 99%